Impact financial ratios and Stock prices in pharmaceutical subsector companies for the 2019-2023 period - Hardika, Andhika Ligar; Saleh, Suji Abdullah; Maryanti, Lilis (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This research aims to explore the impact of the current ratio, debt to equity ratio, and return on assets on share prices in pharmaceutical subsector companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The independent variables tested are current ratio, debt to equity ratio, and return on assets, while the dependent variable is share price. The research sample consisted of 9 pharmaceutical subsector companies selected using the purposive sampling method. Data analysis was carried out using panel data regression analysis with a significance level of 5%, using Eviews 12 software. The research results showed that the current ratio did not have a significant influence on stock prices. However, the debt to equity ratio and return on assets turned out to have a significant effect on the share prices of these companies. Furthermore, together, these three variables influence the share prices of pharmaceutical subsector companies listed on the Indonesian Stock Exchange during the period studied